Relokasi Pasar Tradisional Pulo Brayan Kota Medan dengan Pendekatan Arsitektur Modern - Samudro, Muhammad Bayu; Wisdianti, Dara; Nuraini, Cut (Universitas Medan Area, 2025)
The Pulo Brayan Traditional Market in Medan City has several problems such as inadequate facilities, poor accessibility, and lack of comfort for traders and visitors.This design aims to relocate the traditional market with a modern architectural approach to improve the quality of the market’s infrastructure and services. The design method used is literature study and analysis of modern architectural design that integrates traditional elements with modern materials. The results of the study show that relocating the market with a modern design can create an efficient spatial layout, provide additional facilities such as adequate parking space, and enhance comfort through natural lighting, cross ventilation, and zoning of areas based on the type of goods. Additional facilities, such as a sky bridge and disability-friendly spaces, also provide easier access for all visitors. Furthermore, better waste management contributes to creating a healthy and clean market environment. With this approach, the relocation of the market is expected to enhance the shopping experience, strengthen the market's function as a local economic center, and support environmental sustainability.